Islamic state utopia: investigating khilafatul muslimin movement in contemporary Indonesia - Sukardi, Imam (IAIN Salatiga, 2023)
This article aims to explore the contemporary Islamic state establishment movement in Indonesia namely Khilafatul Muslimin. Even though the Islamic state is strictly forbidden in Indonesia by the national constitution, such movements have been endless for a long time in the country. The phenomenon of Khilafatul Muslimin, which has recently emerged and surfaced in the realm of politics and religion in the country, indicates that some Muslims want to establish a Khilafah state under Islamic law. Utilizing qualitative methods with the library and documents research in a thorough and depth analysis, this article is designed to excavate and identify the anatomy of the Khilafatul Muslimin as the Islamic state movements, which were familiar to the archipelago since its independence. The study reveals that unlike the past similar movements, which mostly ended in the discourse, this organization has built a set of an Islamic state hierarchy and bureaucracy with complete personals. In addition, Khilafatul Muslimin linked its network to those radical-global Islamic state movements like the Islamic State of Iraq and Syria (ISIS), which, in turn, challenges Pancasila as the national ideology. However, interestingly, the root of Khilafatul Muslimin is closely related to Darul Islam (DI) and Negara Islam Indonesia (NII, Indonesian Islamic State), the past and utopian Islamic state movement in a huge multicultural Indonesian society. This research will benefit the policymakers in Indonesia to treat other Islamic movements equitably, while still keeping the country in harmony. For further study, it will be fruitful to involve broader methods in gathering data to have more comprehensive results.